2003
DOI: 10.1295/polymj.35.364
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional Emulsion Polymerization of Methyl Methacrylate. Effect of Cu(II)/Histidine Complex Catalyst and Different Peroxo-Salts

Abstract: ABSTRACT:The characteristics of nonconventional (soap-free) aqueous emulsion polymerization reactions of methyl methacrylate were evaluated by the catalytic effect of in situ developed different transition metal (II) chelate complex with amino acids initiated by different peroxo salts like potassium monopersulfate (KMPS, KHSO 5 ), potassium persulfate (KPS, K 2 S 2 O 8 ), ammonium persulfate (APS, (NH 4 ) 2 S 2 O 8 ). From the comparative data, the CuSO 4 /histidine chelate complex was selected as a novel cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…PSL has charged groups on the surface for monodisperse in electrostatic interactions. [24][25][26][27] The diameter of the PSL can be controlled by 150-500 nm. The diameter and Zeta potential were measured with the Zetasizer Nano ZS (Malvern Panalytical).…”
Section: Fabrication Procedures Of Porous Particlesmentioning
confidence: 99%
“…PSL has charged groups on the surface for monodisperse in electrostatic interactions. [24][25][26][27] The diameter of the PSL can be controlled by 150-500 nm. The diameter and Zeta potential were measured with the Zetasizer Nano ZS (Malvern Panalytical).…”
Section: Fabrication Procedures Of Porous Particlesmentioning
confidence: 99%
“…So in the present work PMMA/SP composites were synthesized by in situ emulsion polymerization method [24] and their oxygen permeability and flame retardancy were studied with variation of soy protein content.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work had shown that the resulting modified fibers showed better thermal stability 10 . These modified PALFs were then grafted with a hydrophobic monomer, methyl methacrylate, using a different complex initiating system Cu (II) / histidine / ammonium persulfate (APS) which had already been used as an effective system in the emulsion homopolymerization of MMA 11 . The commercially important properties of the grafted samples were characterized, focusing special attention on their water absorption, surface morphology, biodegradability, dyeability, etc.…”
Section: Introductionmentioning
confidence: 99%